Tensile, flow and thermal properties of biodegradable PLA/pineapple fiber composite / Hadi Faiz Mohamed - Mohamed, Hadi Faiz (2019)
Human activities and food need to be pack than be transported to the worldwide especially in import export business. The materials that use was very important and had their own shelf-life to deliver most products in its required condition a specification. With regard to environment aspects, it would be beneficial if natural fibres could be used instead of synthetic fibres as reinforcement in some structural and food packaging applications. This research was conducted to determine the tensile, flow and thermal properties of biodegradable PLA/PALF composites. The properties were tested by using testing equipment such as Melt Flow Tester, Fourier Transform Infrared (FTIR), Tensile Tester and Differential Scanning Calorimetry (DSC). Different composition that used in fabrication of PLA and PALF which were 80% PLA - 15%PALF, 70% PLA – 0% PALF and 100% PLA – 0% PALF for controlled.